2017
DOI: 10.5530/ijper.51.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Hepatoprotective Potential and Antioxidant Role of Carob Pods (Cerotonia siliqua L.) against Carbon Tetrachloride-induced Toxicity in Rats

Abstract: Objective: The aims of current study are the evaluation of the protective effect and antioxidant role of carob pods against carbon tetrachloride (CCl 4 )-induced oxidative stress, hepatotoxicity and nephropathy. Material and Methods: The present experiment was designed as I (control), II (0.5 ml/kg CCl 4 ), III (%10 CP), IV (CCl 4 0.5 ml/kg+%10 CP) groups. While rats in group I and III were fed with a diet without CCl 4 , II, and IV groups received twice 0.5 ml/kg/week, where IV group additionally received %10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Based on the results of this study, carob powder can be used as an antioxidant to reduce MDA and inhibit CCl4 production as well as reduce free radicals. 20 In line with these studies, in the present study, the extract of the carob fruit in a specific dose (200 mg/kg) increased the levels of catalase and superoxide dismutase enzymes. The testicular tissue changes in healthy mice are physiologic but not pathologic.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the results of this study, carob powder can be used as an antioxidant to reduce MDA and inhibit CCl4 production as well as reduce free radicals. 20 In line with these studies, in the present study, the extract of the carob fruit in a specific dose (200 mg/kg) increased the levels of catalase and superoxide dismutase enzymes. The testicular tissue changes in healthy mice are physiologic but not pathologic.…”
Section: Discussionsupporting
confidence: 87%
“…The CCl 4 also generates ROS consistently and reduces antioxidant enzymes, leading to lipid peroxidation ( Recknagel et al ., 1989 ; Jaeschke, 2000 ; Zhu and Fung, 2000 ; Weber et al ., 2003 ). In recent studies, CCl 4 -induced animal model showed a significant increase of AST and ALT levels in serum within a short period of time, and the model also showed coagulation necrosis and hepatocyte vacuolation in the hepatic lobules ( Yang et al ., 2008 ; Chen et al ., 2013 ; Kemelo et al ., 2017 ; Suzek et al ., 2017 ). The purpose of this study is to identify the protective activity of ES formulation and to determine the underlying mechanism using the CCl 4 -induced animal models.…”
Section: Discussionmentioning
confidence: 99%
“…reported that carob pod polyphenols (CPPs) had stronger antioxidant effects against the discoloration of β-carotene than catechins and procyanidins [ 3 ]. Furthermore, several in vivo models have demonstrated that carob pods have hepatoprotective effects against carbon tetrachloride-induced toxicity [ 4 ] or ethanol-induced liver injury [ 5 ], gastroprotective effects against ethanol-induced oxidative stress [ 6 ], and antidiabetic effects against alloxan-induced diabetes [ 7 ] or streptozotocin-nicotinamide-induced diabetes [ 8 ]. However, the anti-obesity effect and its mechanism of action have not been clarified.…”
Section: Introductionmentioning
confidence: 99%